Cost Analysis of Battery and Hydrogen Powered Trains on Non-Electrified Regional Railways in Sweden - Andersson,Johan; Wallin,Elliot (CODEN:LUTEDX/TEIE, 2025)
This thesis investigates the cost efficiency of two drivetrain configurations — Battery-Only and Hydrogen-Battery — for use in mini-trains operating on non-electrified rural railways. The study focuses solely on drivetrain-related components, including onboard energy storage, traction systems, and associated infrastructure such as charging stations and hydrogen refueling facilities. A comprehensive literature review was conducted to determine relevant cost parameters, followed by simulation and optimization routines implemented in MATLAB. The cost per train per trip (ptpt) was calculated for various battery capacities and infrastructure configurations, and a sensitivity analysis was performed to evaluate the impact of fluctuating component prices. The results show that Battery-Only conf igurations are consistently cheaper than Hydrogen-Battery alternatives, both in terms of upfront investment and operational expenditure. Depending on the chosen infrastructure setup, the Hydrogen-Battery configurations were found to be between 120% and 173% more expensive per train per trip. However, the study relies on several broad assumptions and considers only drivetrain components in the cost analysis. As a result, the optimization outcomes should be interpreted with caution. The findings should not be viewed as a comprehen sive investment recommendation, but rather as an indicative cost comparison between different drivetrain technologies under simplified conditions.
Keywords: cost analysis; trains; hybrid trains; hydrogen; optimization; charging infrastructure; hydrogen infrastructure; mini trains; non-electrified tracks